1999
DOI: 10.1002/(sici)1097-4636(19990905)46:3<399::aid-jbm13>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxic effect of titanium particles phagocytosed by osteoblasts

Abstract: The cytotoxic effect of different concentrations of titanium particles on osteoblasts was studied in vitro. It was found that the viability of the osteoblasts was inversely proportional to the particle concentration. Phagocytosis of particles by the osteoblasts was evident and was demonstrated to be responsible for cell necrosis. Moreover, during and after phagocytosis, the osteoblasts released products that were cytotoxic for other osteoblasts, as established with a conditioned medium assay. The titanium part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
127
5

Year Published

2000
2000
2002
2002

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 154 publications
(144 citation statements)
references
References 39 publications
10
127
5
Order By: Relevance
“…This result is in opposition to a previous study using Ti particles [17]. The number and the size distribution of particles for both studies were similar.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This result is in opposition to a previous study using Ti particles [17]. The number and the size distribution of particles for both studies were similar.…”
Section: Discussioncontrasting
confidence: 99%
“…The small CPC particles induced an important negative e!ect on osteoblast functions which strongly suggested that the phagocytosis process of CPC particles was involved. Recent "ndings that osteoblasts phagocytosed Ti particles [29] and osteoblasts treated with cytochalasin-D (agent that inhibits phagocytosis by affecting actin "lament assembly of the cytoskeleton) almost completely suppressed the negative e!ect of Ti particle on osteoblast viability [17] supports this hypothesis. As for the macrophages or multinucleated giant cells [19], this phagocytosis process could produce an accumulation of calcium in mitochondria and could eventually lead to lysis of mitochondria and cell death.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…We recently showed that wear particles also influence osteoblast behaviour [6][7][8][9]. Release of metal ions by the implant and their effect on osteoblasts has been mostly neglected until recently [10].…”
Section: Introductionmentioning
confidence: 99%